Pemberdayaan Masyarakat LKSA Aisyiyah Balikpapan melalui Pengembangbiakkan Ikan Lele dengan Pakan Otomatis: Community Empowerment of Aisyiyah Balikpapan LKSA through Catfish Breeding with Automatic Feeding - Saputra, Riza Hadi; Dewanto, Muhammad Ridho; Rosalina, Rosalina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Catfish breeding using an automatic feeding system involves four crucial stages to achieve success in this endeavor. The first stage in this process is the survey stage, which involves a field survey by visiting the Aisyiyah Children's Social Welfare Institution (LKSA). The second stage is the tool preparation stage. This process begins with purchasing the necessary equipment based on the results of the survey that has been conducted. The third stage is the tool installation stage. This stage begins with the land preparation, including leveling the land where the catfish ponds will be installed. As a further step, bricks are used around the perimeter of the catfish pond to support the pond foundation and prevent collapse. Then, an automatic feed device was installed to support the automatic feeding system according to a predetermined schedule. The last stage is the equipment handover stage. This stage marks the completion of the installation and preparation process and signifies the start of the active phase in catfish farming using the automatic feed system. Success in the implementation of each of these stages has direct implications for the success and sustainability of the catfish farming business at LKSA Aisyiyah.